Site as playground: expanding the experience of play - Melvin, Rebecca (Kansas State University, 2012)
Encouraging creativity is an important part of a child’s education and often not adequately supported by outdoor school environments. Contemporary playgrounds are designed in response to perceptions of liability and a limited interpretation of child development. Prefabricated plastic constructions and expanses of asphalt are poor initiators of creative expression. This project proposes a more stimulating, artistically crafted alternative to the typical playground. Beginning with documented research of play, the project layers psychology, education and humanities to form an understanding of how formal space affects human experience. More specifically, poetry, land art, sculpture, narrative and character studies inform the design solution for a 6.4 acre site at Northview Elementary School in Manhattan, Kansas. Integrated design provides children a meaningful experience of space and direct contact with nature. This design encourages imaginative and creative play, expanding the experiential quality of a contemporary playground.
Keywords: Landscapes of learning; Creativity; Playground design; Experiential learning; Play; Childhood development; Landscape Architecture (0390)